Doubts on Avicenna A Study and Edition of Sharaf al-Dīn al-Masʿūdī's Commentary on the Ishārāt - Shihadeh, Ayman (Islamic Philosophy, Theology and Science. Texts and Studies, 2015)
In Doubts on Avicenna, Ayman Shihadeh offers an extended study and critical edition of Sharaf al-Dīn al-Masʿūdī's al-Mabāḥith wa-l-Shukūk, a key and hitherto unstudied source for twelfth-century Arabic philosophy. This text inaugurates the long commentarial tradition on Avicenna's Ishārāt. Readership: All interested in the history of medieval Arabic philosophy and rational theology (kalām), especially metaphysics, natural philosophy, Avicenna, the Avicennan tradition, al-Ghazālī, Abū l-Barakāt al-Baghdādī and Fakhr al-Dīn al-Rāzī.